How to effectively design and create a concept mobile application to aid in the management of type 1 diabetes in adolescents. (3rd July 2017) - McCulloch, Victoria; Hope, Sarah; Loranger, Brian; Rea, Paul
Abstract: Diabetes is one of the most prevalent chronic health conditions in the world; with a range of diabetes-related mobile applications available to the public to aid in glycaemic control and self-management. Statistically, adherence to medication is extremely low in adolescents with Type 1 Diabetes Mellitus (T1DM), therefore, this paper focuses on the research and design of an interactive and educational concept mobile application aimed at early to mid-adolescents to aid in their understanding of T1DM. As visual elements are an essential part of the design, this research outlines how visual components were designed specifically for adolescents with T1DM.